Eksistensi Dan Reformasi Kebijakan Hubungan Ketenagakerjaan Dalam Pemenuhan Serta Perlindungan Hak-Hak Pekerja Atas Sistem Pengupahan Di Indonesia - Rastini; Pamardisiwi, Tiara Awanisa; Baiquni , Muhammad Iqbal (Universitas Muhammadiyah Yogyakarta, 2022)
Labor law or what is currently known as labor law contains basic rules that protect the rights and obligations of workers such as the right to wages, the right to placement work, and the right to equal treatment. In the reform era, the implementation of laws and regulations has become more democratic, transparent and seeks to realize good governance by protecting human rights which have an impact on the Industrial Relations system in Indonesia. Labor unions are a means of industrial relations which are explicitly stated in Law no. 13 of 2003 which is used as a means of struggle for workers to protect the rights and interests of workers. However, the many failures of trade unions in fighting for labor rights have resulted in the loss of the trust of workers who are fighting to get their rights back and lose confidence in freedom of expression. The struggle of the workers is caused by the inconsistency of regulations regarding the rights and obligations of workers which in reality makes many workers feel disadvantaged a reform of workers' rights is needed as contained in Law Number 13 of 2003 concerning Manpower. The reform is intended not to undermine the rights of workers and continue to fulfill their obligations as workers. Writing this article aims to provide new relevance regarding the reform of labor rights contained in Law Number 13 of 2003 concerning employment. The writing of this work uses normative legal research and uses a statutory approach or Statute Approach.